A method for controlling crowd flow by changing recommender information on navigation application. Issue 1 (4th April 2016) - Shen, Ruiwei; Terada, Tsutomu; Tsukamoto, Masahiko
Abstract : Purpose: This paper aims to control the crowd flow naturally by presenting appropriate information. Design/methodology/approach: The authors developed a navigation application for an event held in Osaka called "Osaka Mizube Bar", and divided users into three groups to present different information in restaurants' view list. Findings: The results of the experiment confirmed that users will focus on the position of the rank list, regardless of the information for each item. Originality/value: This paper used persuasive technology in information presentation for event application.